Study on cracking resistance of polyvinyl alcohol fiber-reinforced low-dose cement-stabilized crushed stone - Xin Yan; Zhigang Zhou; Jian Jin (Archives of Civil Engineering)
In this paper, the effects of polyvinyl alcohol fiber incorporation on the crack resistance of low-dose cement-stabilized crushed stone have been investigated. The resulting change in the compressive strength, compressive rebound modulus, splitting strength, dry shrinkage factor, and impact toughness with fiber incorporation was evaluated through the unconfined compressive strength test, compressive rebound modulus test, crack strength test, dry shrinkage test, and impact toughness test. The results showed the positive influence of PVA fibers on the crack resistance of low-dose cement-stabilized crushed stone. PVA fibers have been shown to improve the compressive strength, splitting strength, and impact toughness of low-dose cement-stabilized crushed stone while reducing the compressive rebound modulus and dry shrinkage factor. With the increase of fiber incorporation, the compressive strength, splitting strength, and impact toughness tend to increase first and then decrease. The compressive resilience modulus and dry shrinkage coefficient showed a tendency to decrease first and then increase. When the fiber dosage is 0.9 kg/m3, the maximum energy consumed in the fracture of the specimen, the strongest impact resistance and impact ductility of the material, the indexes reach the optimal value, indicating that the crack resistance of PVA fiber low-dose cement-stabilized crushed stone is optimal at this dosage. This study provides a theoretical basis for promoting and applying PVA fiber in low-dose cement-stabilized gravel.